Planning for Cultivation Numerical Literacy in Mathematics Learning for Minimum Competency Assessment (AKM) in Elementary Schools - Rohmah, Aldila Nur; Sutama, Sutama; Hidayati, Yulia Maftuhah; Fauziati, Endang; Rahmawati, Laili Etika (Universitas Pendidikan Indonesia, 2022)
Numeracy literacy skills in learning mathematics in elementary schools are still low. This is evident from the AKM value, which is still below average. This low numeracy literacy ability is caused by various things, such as the teacher's lack of ability to make HOTS questions and the lack of habituation for students to work on complex. The main problem that causes students to be still unable to complete learning based on numeracy literacy is the teacher who has not familiarized students with literacy-based questions. Many teachers still cannot compile numeracy literacy questions, especially at the elementary school level. This research is qualitative research with a case study. The results of this research are planning for curricular activities in cultivating numeracy literacy carried out by compiling a Learning Implementation Plan (RPP), compiling numeracy literacy-oriented learning materials, compiling numeration literacy-oriented evaluation questions with the criteria of Higher Order Thinking Skill (HOTS), and designing audio-visual and realistic learning media.